Transmission of Methicillin-Resistant Staphylococcus aureus between Human and Hamster - Ferreira, Jorge Pinto (American Society for Microbiology, 2011)
Transmission of methicillin-resistant Staphylococcus aureus (MRSA) between humans and animals is increasingly recognized. We newly document that the transmission of MRSA between human and hamster is possible.